Utilização do método Analytic Hierarchy Process (AHP) para localização de usina de reciclagem de resíduos da construção civil - Silva, Mayara Cristina Ghedini da (2012)
This research aimed to propose a methodology for identifying potential sites to locate a waste recycling plant of Civil Construction in Ponta Grossa city. For this, presenting a background on: sustainability and sustainable development; CONAMA Resolution; ABNT rules and municipal laws, which impose criteria for the establishment of the plant for recycling them. Seeking to answer the specific objectives of this study, the methodology applied was divided into five stages, namely: bibliographic and documentary, to select criteria and sub criteria; criteria validation, definition of alternatives; development of the hierarchical structure and application of the model in software Expert Choice 11.5. With this work, it was developed a applicable methodology in different cities, which have as their objective the establishment of a recycling plant. The Analytic Hierarchy Process (AHP) method allowed to transform qualitative informations into quantitative, so facilitating decision making processes. Can be concluded that with the application of AHP method which the criterion Environmental Pillar presents itself as a major factor in decision making and the land located in the Uvaranas neighborhood, presents itself as the alternative with the greatest potential to locate a waste recycling plant of Civil Construction in Ponta Grossa city.